Application of Discovery Learning Method as An Effort to Improve Learning Outcomes of Fikih Zakat Fitrah Material Class V C In MIN 2 Kediri City - Much Rosyidi; Ahid, Nur; Khoiri, M. Alim; Saifullah; Ilham Tohari (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
In order to improve the learning outcomes of students in the Islamic jurisprudence subject Zakat Fitrah material in Kediri City, it is necessary to conduct classroom action research to obtain the significance of the influence of the Discovery Learning learning model on student learning outcomes, especially in the fiqh subject class Vc MIN 2 Kedirim City. The results of this research showed that the average score in the pre-cycle was 72.35 with a completion percentage of 64.7%. The learning results after carrying out the second cycle research by applying the discovery learning method to the learning of Islamic law regarding Zakat fitrah provisions, namely Total Value = 2580, Average Value = 75.88, and Learning Completeness = 91.2%. Based on the research results from Cycle 1 and Cycle 2, it can be concluded that the use of the learning model is effectively applied in learning ZakatFitrah materials.